The effects of postoperative delirium on outcomes in hip fracture patients (UCC Student Medical Journal, 2024)
Background: Hip fractures have reached epidemic levels in an ever-ageing population. Based on this increase, the rate of postoperative delirium (POD) is simultaneously expected to rise as it seems to be a disproportionate hazard post-hip surgery. POD is purported to have detrimental effects, but prevention and screening efforts remain inadequate. Therefore, examination of recent evidence for negative outcomes, including decreased survival and increased complications, is critical if we seek best practice. Objectives: This review examines the most recent evidence for the effect of POD on mortality of hip fracture patients and other outcomes such as length of stay, discharge destination and functional outcomes. Methods: Two electronic database searches resulted in selection and critical appraisal of ten studies. Results: Across the ten articles selected for review, the prevalence of POD ranged from 18-53.3%. Nine studies focused on mortality. In unadjusted analysis, mortality was found to have a significantly increased association with POD. However, several papers showed with effective adjustment for confounding or contributory variables, no independent association was observed. Medical complications was a focus in four of the articles, and the association with POD was observed following adjustment. Similar results were reported for increased non-home discharge and length of hospital stay. Conclusion: POD has some effect on outcomes in hip surgeries but future research needs coherence of methods across the field and comprehensive accounting for the increased age and comorbidities of POD patients. Determining whether factors like increased length of stay are themselves the cause, rather than the result, is imperative. The lack of consistent high-quality research frustrates the validity of many of the papers conclusions on increased mortality. While we await such research an effort still needs to be made to prevent POD, especially given the more valid evidence of other less fatal effects.
Keywords: postoperative delirium; hip fracture; hip surgery